2018
DOI: 10.1089/can.2018.0065
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Cannabinoid Activity Against Colorectal Cancer Cells

Abstract: Introduction: Colorectal cancer (CRC) is a leading cause of cancer-related deaths worldwide, and new therapeutic strategies are still required. Here we screened a synthetic cannabinoid library to identify compounds that uniformly reduce the viability of seven CRC cell lines.Material and Methods: Seven distinct CRC cell lines were treated with 10 μM cannabinoid compounds (from a library of 370 molecules) for 48 h, and cell viability was subsequently measured with MTS assay. Dose–response curves were conducted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…Interestingly, treatment with ∆9-THC (10 µM) or CBD (10 µM) was either ineffective or much less potent and only partially efficacious. Moreover, treatment with CB1, CB2, GPR55, and/or TRPV1 antagonists (alone or in combination) failed to block the activity of the most potent identified compounds, suggesting that its action is independent of the activation of canonical receptors [54].…”
Section: Gastrointestinal Cancersmentioning
confidence: 99%
“…Interestingly, treatment with ∆9-THC (10 µM) or CBD (10 µM) was either ineffective or much less potent and only partially efficacious. Moreover, treatment with CB1, CB2, GPR55, and/or TRPV1 antagonists (alone or in combination) failed to block the activity of the most potent identified compounds, suggesting that its action is independent of the activation of canonical receptors [54].…”
Section: Gastrointestinal Cancersmentioning
confidence: 99%
“…The final DMSO concentration was 1% in all conditions. Viability was measured after 48 hours using the MTS ((3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium) assay (Biovision; Milpitas, CA) [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…For all treatments the final DMSO concentration was 1%. After 48 hours cell viability was assessed using the MTS assay (Biovision; Milpitas, CA) as previously described [ 35 ]. Viability was calculated by normalizing each cell line to vehicle treatment alone.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro and in vivo studies provide evidence that suggests efficacy of cannabinoid agonists in reducing tumor growth and proliferation [19]. Δ 9 -THC has been used as an approved treatment for cancer patients with AIDS experiencing chemotherapy-induced nausea, vomiting, and anorexia [78]. Additionally, cannabinoids have shown to have significant benefit cancer-associated pain and has shown a synergistic effect when combined with opioid analgesics [5].…”
Section: Cancers: Colorectal Cancer (Crc)mentioning
confidence: 99%
“…Additionally, cannabinoids have shown to have significant benefit cancer-associated pain and has shown a synergistic effect when combined with opioid analgesics [5]. A recent study has identified synthetic cannabinoid compounds that reduce colorectal cancer (CRC) cell viability mediated by an unknown mechanism [78]. American Journal of Plant Sciences Colorectal cancer, the third most common cause of cancer death, is characterized by mutations in the adenomatous polyposis coli (APC), KRAS, and p53 genes [79].…”
Section: Cancers: Colorectal Cancer (Crc)mentioning
confidence: 99%